Zakat on employment income : awareness, understanding & compliance / Shafinah Abd Rahim - Abd Rahim, Shafinah (2013)
Colonization has divided the Muslims into two groups as far as the understanding of zakat income is concerned. One (unfortunately the bigger), which considers paying taxes as sufficient to cover their zakat obligation and the other consisting of those who fulfill their religious obligation as an addition to the compulsory taxes of the conventional fiscal policy.